2012
DOI: 10.1002/anie.201108850
|View full text |Cite
|
Sign up to set email alerts
|

Traceless Tosylhydrazone‐Based Triazole Formation: A Metal‐Free Alternative to Strain‐Promoted Azide–Alkyne Cycloaddition

Abstract: Triple‐T trick! Traceless tosylhydrazone‐based triazole formation is readily achieved by reacting primary amines with functional α,α‐dichlorotosylhydrozones under ambient conditions. This fast and efficient alternative affords exclusively 1,4‐substituted triazole “click products” with complete retention of configuration. Primary amines, inherent to many natural products, can be modified in this way without protecting group manipulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(43 citation statements)
references
References 51 publications
0
42
0
1
Order By: Relevance
“…[9] In 1986, Sakai et al reported the synthesis of substituted 1,2,3-triazoles 11 through the reaction of an a,a-dichloroketone 10, tosylhydrazide and a primary amine (Figure 1 b). [10] The scope of this transformation was explored by Westermann and co-workers [11] and demonstrated on scale by Hanselmann et al, [12] providing a novel process to form this heterocyclic core. However, several limitations exist with this method.…”
mentioning
confidence: 99%
“…[9] In 1986, Sakai et al reported the synthesis of substituted 1,2,3-triazoles 11 through the reaction of an a,a-dichloroketone 10, tosylhydrazide and a primary amine (Figure 1 b). [10] The scope of this transformation was explored by Westermann and co-workers [11] and demonstrated on scale by Hanselmann et al, [12] providing a novel process to form this heterocyclic core. However, several limitations exist with this method.…”
mentioning
confidence: 99%
“…11,12 However, a similar breakthrough has still not been made in the synthesis of pyrazoles. Herein, we report an unprecedented N-N coupling strategy for the synthesis of 1,3,4-trisubstituted pyrazoles via [4+1] cyclization from α-(1,3-dithian-2-yl) enamine ketones and primary amines (Scheme 3).…”
Section: Scheme 1 Copper(ii)-catalyzed Oxidative N-n Bond Formationmentioning
confidence: 99%
“…Metal-free triazole synthesis was also reported by the modification of Sakai reaction of an amine and α,α-dichlorotosylhydrazones [14]. On the basis of these observations and our continued interest to develop novel heterocycles [15,16] it is proposed to construct new molecules having pyrazole and 1,2,3-triazole motifs at 1,3-positions of the phenyl moiety and to study their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 96%